Perancangan Sistem Informasi Manajemen Berbasis Website Pada Program Studi Teknik Industri Universitas Mulawarman - Isal, Andi; Yudi Sukmono; Harjanto, Arif (Jurnal Teknik Industri (JATRI), 2023)
The current advancement in information technology has had a significant impact on information provision and management. The presence of the internet as the primary medium for accessing information has become a fundamental necessity in modern society. In the context of higher education, the Industrial Engineering Program is not exempt from challenges in disseminating and efficiently managing information. Vital information often gets scattered and is difficult to access, especially when conveyed through conventional methods such as physical bulletin boards or WhatsApp messages. This research is conducted using in-depth interviews with various stakeholders, including program chairs, administrative staff, faculty, and students. The findings of this research strongly indicate the need for the development of a more efficient information management system within the Industrial Engineering Program. As a proposed solution, a website will be developed with various key features, including announcement management, curriculum information, schedule management, administrative management, guidance management, and document archiving. The implementation of this system is expected to address several identified issues, such as limited accessibility to important information and inefficient management. Thus, the operational efficiency of the Industrial Engineering Program is expected to be significantly enhanced. The results of this research highlight the importance of adapting information technology in the constantly evolving context of higher education. In an era where information technology continues to advance, efforts to utilize it optimally in information management within educational institutions like the Industrial Engineering Program remain highly relevant. An efficient information management system can provide substantial benefits in enhancing the quality of information management within the Program